Measurement model of the influence of strategic management accounting on the growth of drinking water companies in South Kalimantan - Rahman, Yudi; Ujianto, Ujianto; Cempena, Ida Bagus (Edelweiss Applied Science and Technology, 2024)
This study discusses strategic human resource management in Regional Drinking Water Companies (PDAM) in South Kalimantan, focusing on operational challenges and dynamics of clean water management. This study uses quantitative methods with SEM PLS analysis to evaluate company efficiency, performance, and growth. Data were collected from four PDAMs representing various districts, covering 153 respondents. The results of the analysis show that company efficiency has a significant effect on growth, with T-Statistics 4.414 and P-Value 0.000. In addition, company performance is proven to affect efficiency (T-Statistics 8.820, P-Value 0.000) and growth (T-Statistics 2.696, P-Value 0.007). The application of strategic management accounting also contributes positively to efficiency (T-Statistics 2.670, P-Value 0.008) and growth (T-Statistics 2.605, P-Value 0.009). Mediation analysis shows that company performance and efficiency play a role in linking strategic management accounting to growth. This study provides important insights for PDAM management to implement strategic management accounting practices to improve efficiency, performance, and sustainable growth in facing challenges in the public service sector.